The Attitude and Views of Aswaja An Nahdliyah Regarding Brotherhood Between Islamic Organizations - Joko Subando; Joko Sarjono; Nashrudin Baidan; Abyanudin al Java; Batul Rizka Afifah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to construct the attitudes and views of Aswaja An Nahdliyah on brotherhood among Islamic organizations. This study is qualitative and utilizes a case study design. The data needed includes NU's attitudes and views on brotherhood, sourced from various Aswaja books used for internalization in Ma’arif education, articles, writings on NU's website, and videos from the NU online channel. Data is collected documentarily and analyzed descriptively according to themes, with findings validated through interviews with NU administrators. The results show that Ukhuwah Islamiyyah, from the perspective of Aswaja An Nahdliyah, represents unity and brotherhood due to shared beliefs and religious practices, common concepts of nationalism, and shared practical political interests. The findings of this research can serve as a foundation for developing instruments to measure the Ukhuwah Islamiyyah among Islamic organizations.